2010
DOI: 10.1364/oe.18.018206
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the efficiency of slit-coupling to surface-plasmon-polaritons via dispersion engineering

Abstract: Abstract:We describe a simple method for enhancing the efficiency of coupling from a free-space transverse-magnetic (TM) plane-wave mode into a surface-plasmon-polariton (SPP) mode. The coupling structure consists a metal film with a dielectric-filled slit and a planar, dielectric layer on the slit-exit side of the metal film. By varying the dielectric layer thickness, the wavevector of the SPP mode on the metal surface can be tuned to match the wavevector magnitude of the modes emanating from the slit exit, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 15 publications
2
19
1
Order By: Relevance
“…The free-space light and SP resonance mode coupling efficiency 30,54 often affects the EOT intensities. Both experimental and FDTD-calculated results indicate an enhanced red light relative to the green light as expected.…”
Section: Resultsmentioning
confidence: 99%
“…The free-space light and SP resonance mode coupling efficiency 30,54 often affects the EOT intensities. Both experimental and FDTD-calculated results indicate an enhanced red light relative to the green light as expected.…”
Section: Resultsmentioning
confidence: 99%
“…al. 34. It is observed that the absolute contribution of the intensity due to surface plasmons remains almost the same in both the nanohole and microhole apertures.…”
mentioning
confidence: 85%
“…Therefore, how to elevate or what factors will affect the launching efficiency of SPP is inevitably a very important issue. Recently, many SPP-based metallic nanostructures with different designs have been proposed and studied in both theory [1][2][3][4][5] and experiment [6][7][8][9] and attempted to solve this problem. However, these complex structures are usually very hard to fabricate in practice.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, how to effectively and easily improve the intensity and efficiency of SPP becomes much more needed. On the other hand, the surrounding dielectric medium of subwavelength apertures is also a significant factor to influence the SPP excitation [3,4], but less attention has been paid to either this parameter or the electromagnetic behavior generated in structures with this parameter, such as interference, which would affect the calculated accuracy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation